Evaluation of the performance of immunoblot and immunodot techniques used to identify autoantibodies in patients with autoimmune diseases - EL Hassouni Youssef (De Gruyter, 2021)
Autoimmune diseases are pathological conditions in which the immune system mistakenly attacks its own tissues. This study evaluates the performance of two techniques, which are identifiers of autoantibody specifics: immunoblot and immunodot. This study was conducted in 300 patients of whom 62 were tested positive for antinuclear antibodies. The patients were initially screened for antinuclear antibodies using indirect immunofluorescence. Then, the identification of specific autoantibodies such as anti-extractable nuclear antigens (ENAs) was carried out using the immunoblot and immunodot techniques. The results showed that immunoblot and immunodot did not present a significant difference in their sensitivity against anti-SSA/52, SSB, CENP-B, PCNA, U1-snRNP, Jo-1, Pm-scl, and Mi-2 (p > 0.05). However, the two techniques showed a significant difference in their sensitivity toward autoantibodies anti-DNAn, anti-histone, anti-SmD1, and anti-ds-DNA (p < 0.05). The immunoblot data were in complete accordance with the immunodot data (100%) regarding the detection of autoantibodies such as anti SSA/52, SSB, CENP-B, PCNA, U1-snRP, Jo-1, Pm-scl, and Mi-2, 80% regarding SmD1, and 75% concerning ds-DNA. We should certainly pay closer attention to the efficiency of the techniques used in the diagnosis of autoimmune diseases.